1994
DOI: 10.1139/z94-137
|View full text |Cite
|
Sign up to set email alerts
|

A mass budget for transgenic "Supermice" engineered with extra rat growth hormone genes: evidence for energetic limitation

Abstract: Genetically engineered "Supermice" (Mus musculus, transgenic strain Tg[MT-1,rGH],Bri2) possess multiple copies of rat growth hormone genes yielding growth rates 220% that of normal mice. To discover how Supermice alter their acquisition and allocation of resources under elevated costs of growth, a resource allocation study was conducted on forty 50-day-old normal and transgenic male mice. Individual dry mass budgets were used to compare rates of growth, consumption, faecal deposition, digestive assimilation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…We observed higher concentrations of these products than in normal mice. The life span of the transgenic mice in the study was also reduced to half that of normal animals (Kajiura and Rollo, 1994). Although it is uncertain how extra GH may increase oxidative stress, high levels appear to reduce the influence of insulin on glucose uptake in adipose tissue at a site down stream from the insulin receptor.…”
Section: Introductionmentioning
confidence: 84%
“…We observed higher concentrations of these products than in normal mice. The life span of the transgenic mice in the study was also reduced to half that of normal animals (Kajiura and Rollo, 1994). Although it is uncertain how extra GH may increase oxidative stress, high levels appear to reduce the influence of insulin on glucose uptake in adipose tissue at a site down stream from the insulin receptor.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, rapid growth requires increased reading of DNA which increases damage to DNA; accumulation of error in DNA has been implicated in the senescence of animals (Hart and Setlow 1974). Strains of rodents selected for rapid growth have shorter lifespans and greater tumor production than control strains, lending support to these ideas (Eklund and Bradford 1977;Kajiura and Rollo 1994). Bradford and Famula (1984) noted that the same strains have an unusual susceptibility to external parasites suggesting that they also have poorly developed immune systems (see below).…”
Section: Maintenance and Repairmentioning
confidence: 99%
“…"Supermice" contain multiple copies of rat growth hormone genes and grow twice as fast as untransformed mice. But because this increased growth rate is achieved with a slightly lower mass-specific feeding rate (Kajiura and Rollo 1994), tradeoffs should be apparent. Supermice make up for the energetic cost of rapid growth by spending significantly more time asleep and are less active when awake than wildtype siblings (Lachmansingh and Rollo 1994).…”
Section: Behaviormentioning
confidence: 99%
“…Such a large genetic variation in growth rates implies that trade-offs with fast growth are present (Arendt 1997;Angilletta et al 2003). Trade-offs between growth and reproduction (e.g., Reznick 1982;Anthony et al 1991), maintenance/repair (e.g., Hawkins 1991;Kajiura and Rollo 1994), defense (e.g., Smoker 1986;Arendt et al 2001), and behavior (e.g., Wieser et al 1988;Billerbeck et al 2001) have been demonstrated in a variety of taxa.…”
Section: Introductionmentioning
confidence: 99%